2021
DOI: 10.1093/jjco/hyab038
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with facilitating advance care planning based on the theory of planned behaviour

Abstract: Background In Japan, educational support for advance care planning is still limited, and the factors facilitating advance care planning practice have not been identified. The aim of this study is to identify the factors associated with advance care planning practice in Japan using the theory of planned behaviour. Methods We conducted a cross-sectional study through a nationwide online questionnaire survey with 446 Japanese re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…The results revealed that the participants' behavioral intentions were affected by age, subjective norms, and experience seeing or using ventilators. 9 However, our results support the theory of reasoned action, which suggests that individuals' knowledge contributes to their attitudes and that attitudes and subjective norms determine behavioral intention. 17 Therefore, it is essential to raise public awareness of ACP.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The results revealed that the participants' behavioral intentions were affected by age, subjective norms, and experience seeing or using ventilators. 9 However, our results support the theory of reasoned action, which suggests that individuals' knowledge contributes to their attitudes and that attitudes and subjective norms determine behavioral intention. 17 Therefore, it is essential to raise public awareness of ACP.…”
Section: Discussionsupporting
confidence: 67%
“…A Japanese study used the theory of planned behavior as a framework and conducted a questionnaire survey of 446 people aged 20 years or older. The results revealed that the participants' behavioral intentions were affected by age, subjective norms, and experience seeing or using ventilators 9 . However, our results support the theory of reasoned action, which suggests that individuals' knowledge contributes to their attitudes and that attitudes and subjective norms determine behavioral intention 17 .…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…According to the theory of planned behaviour, individuals will consider the behavioural preference, which is determined by their behavioural attitude, subjective norms and perceived behavioural control before trying to produce a certain behaviour (Young et al, 1991). As shown in Figure 1, these three variables, which have been widely validated in understanding individual behaviour (Takeshita et al, 2021;Yang et al, 2022) Clinical nurses with a low ACP practice preference may be reluctant to lead or participate in ACP discussions with patients and surrogate decision makers, or to expend effort in developing ACP skills and addressing barriers to ACP discussions (Gilissen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to TPB, individual behavior is mainly determined by behavioral attitude, subjective norm, and perceived behavioral control. These 3 variables are affected by their corresponding potential cognitive bases and have been widely validated in the field of understanding individual behavior 26 (Figure). Behavioral beliefs are defined as conscious tendencies about the outcome of behavior.…”
mentioning
confidence: 99%